Auditoría de gestión al talento humano de la Unidad Educativa Fiscomisional San Juan Bautista del cantón Catamayo, periodo 2022. - Piedra Eras, Priscilla Alejandra (2024)
This Curricular Integration Work is entitled “Management Audit of the Human Resources of the Unidad Educativa Fiscomisional San Juan Bautista of Catamayo Canton, period 2022”, arises with the need to determine possible deficiencies or deviations that affect the normal development of the activities of the Human Resources staff within the educational system, that is why, the objectives proposed in this work are aimed at conducting a management audit, determined to be fulfilled in several phases, including planning, which consists of visiting the educational institution, applying techniques such as interviews to the staff that is part of the Human Resources Area, the results obtained helped to gather information related to the management in this area and also allowed to comply with the first objective which consists in the development of the internal control evaluation, whose purpose is to verify compliance with the legal and regulatory provisions in force, the same that begins with the application of the internal control questionnaire, resulting in few weaknesses as they are in the management - administrative subcomponents, and that allow to accumulate information on the functioning of existing controls to determine the weak and strong points in relation to the level of risk that each of these areas presented. With the second objective, management indicators were applied to establish the level of efficiency and effectiveness, achieving an analysis of the situation of the institution in terms of compliance with the planning carried out by the Human Resources Area, allowing an exhaustive analysis of the current situation of the institution, corroborating the absence of significant findings, considering that the educational institution is at a very good level of qualification, with regard to the development of its activities. As a result of the Human Resources Management Audit, it is indicated that the internal control maintained by the institution has some deficiencies, among the main ones are: not having adequate and efficient space to provide first aid care to staff who need it and the lack of a SWOT analysis, the final report is brought to the attention of the director of the educational institution with the respective conclusions and recommendations in order to take timely and appropriate measures to contribute to the progress, development and good living of the staff of this prestigious educational institution.